Optimization of a Web-Based Sweeping Order System Using Supply Chain Management Approach - Putri Aulia; Nugraha Nugraha; Anggun Fergina (bit-Tech, 2026)
The order consolidation process, specifically "sweeping orders," is a critical yet often overlooked upstream activity in Supply Chain Management (SCM). At PT Flexo Solusi Indonesia, reliance on manual spreadsheet-based tools resulted in significant data fragmentation, entry errors, and processing delays, which severely hindered downstream logistics coordination and decision-making. This study aims to address this gap by designing and implementing a web-based sweeping order system integrated with SCM principles. Unlike typical inventory-focused systems, this research conceptually shifts the focus to "pre-processing" data synchronization to ensure early-stage supply chain integrity. The system development followed the Waterfall model, supported by a qualitative case study involving in-depth observation and interviews. To ensure research rigor, the system underwent comprehensive black-box testing and workflow validation, specifically evaluating indicators such as data accuracy, process traceability, and the elimination of redundant entry tasks. The results demonstrate that the centralized system successfully enforces sequential workflow validation, thereby mitigating data inconsistency risks and enhancing information flow between the warehouse, production, and shipping divisions. This study concludes that digitalizing upstream order consolidation is a prerequisite for achieving broader supply chain agility. It contributes to existing SCM literature by providing empirical evidence that operational efficiency is contingent upon the accuracy of initial data processing, serving as a scalable digital transformation blueprint for manufacturing SMEs.